Regulation of gene transfection by cell size, shape and elongation on micropatterned surfaces. Issue 21 (20th May 2021) - Wang, Yongtao; Yang, Yingjun; Yoshitomi, Toru; Kawazoe, Naoki; Yang, Yingnan; Chen, Guoping
Abstract : Cell morphology controlled by micropatterns had different influences on gene transfection. Cell size and aspect ratio could increase gene transfection efficiency, while cell shape showed no influence. Abstract : Gene transfection has been widely studied due to its potential applications in tissue repair and gene therapy. Many studies have focused on designing gene carriers and developing novel transfection techniques. However, the influence of cell size, shape and elongation on gene transfection has rarely been investigated. In this study, poly(vinyl alcohol)-micropatterned surfaces were prepared to precisely manipulate the size, shape and elongation of mesenchymal stem cells, and the influences of these factors on gene transfection were investigated. Cell size showed a significant influence on gene transfection. Elongation could affect the gene transfection of large cells but not small cells. Cells with a large spreading area and high aspect ratio showed high transfection with exogenous plasmid DNA. In particular, the transfection efficiency was the highest in micropatterned cells with a spreading area of 5024 μm 2 and an aspect ratio of 8 : 1. In contrast, cell shape had no significant influence on gene transfection. The different influences of cell size, shape and elongation were correlated with their respective impacts on cytoskeletal structures, cellular nanoparticle uptake and DNA synthesis. Cells with a large size and elongated morphology showed well-organized actin filaments with a high cellular modulus, therefore promoting cellular nanoparticle uptake and DNA synthesis. Cells with different shapes showed similarities in actin filament organization, cellular modulus, uptake capacity and DNA synthesis. The results suggest the importance of cell size and elongation in exogenous gene transfection and should provide useful information for gene transfection and gene therapy.